2018
DOI: 10.1063/1.5025028
|View full text |Cite
|
Sign up to set email alerts
|

Probing dynamics of micro-magnets with multi-mode superconducting resonator

Abstract: In this work, we propose and explore a sensitive technique for investigation of ferromagnetic resonance and corresponding magnetic properties of individual micro-scaled and/or weak ferromagnetic samples. The technique is based on coupling the investigated sample to a high-Q transmission line superconducting resonator, where the response of the sample is studied at eigen frequencies of the resonator. The high quality factor of the resonator enables sensitive detection of weak absorption losses at multiple frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…The operation frequency for screening of a spin wave by a superconductor is limited by the superconducting gap frequency which is typically in sub-THz range. 34 We presume that the limiting in-plane magnetic field, i.e., magnetic field aligned along the surface, for effective screening is the second critical field for type two superconductors. Indeed, while above the first critical field magnetic flux penetrates into a superconductor with vortices, the superconducting surface retains its screening capabilities for Oe fields.…”
Section: Resultsmentioning
confidence: 99%
“…The operation frequency for screening of a spin wave by a superconductor is limited by the superconducting gap frequency which is typically in sub-THz range. 34 We presume that the limiting in-plane magnetic field, i.e., magnetic field aligned along the surface, for effective screening is the second critical field for type two superconductors. Indeed, while above the first critical field magnetic flux penetrates into a superconductor with vortices, the superconducting surface retains its screening capabilities for Oe fields.…”
Section: Resultsmentioning
confidence: 99%
“…A natural initial guess for the origin of the effect of superconducting proximity in S-F-S systems on magnetization dynamics is the Meissner screening of external field, the so-called lensing effect [18,27]. For instance, one could employ fluxometric or magnetometric demagnetizing factors [28,29] of the system for estimation of a hypothetical diamagnetic moment in Nb layers that induces magnetostatic field H a . However, this estimation is not required since the following set of unfulfilled conditions points towards irrelevance of the lensing effect in discussed experiments.…”
Section: Discussion: Possible Origin Of Proximity-induced Anisotmentioning
confidence: 99%
“…Such a spin orientation can possibly produce stray fields of a required direction along magnetization in the F layer. Yet, owing to thin-film geometry and small demagnetizing factors [28,29] of the system an implausibly large magnetization of the spin-polarized area is required for induction of the observed H a , which is far above superconducting critical fields.…”
Section: Discussion: Possible Origin Of Proximity-induced Anisotmentioning
confidence: 99%
“…Microwave experiments in quantum magnonics are typically performed at milli-kelvin temperatures, often using setups equipped with superconducting quantum circuits. On the other hand, a development of various hybrid devices is taking place based on superconducting resonators 7,12 and Josephson junctions [13][14][15] . Also, it was shown that hybridization of a magnon medium with superconducting structures results in substantial modification of dispersion properties [16][17][18][19] , as well as in the formation of magnonic band structures 20 .…”
Section: Introductionmentioning
confidence: 99%